2012
DOI: 10.1200/jco.2011.37.4025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long-Term Serum Platinum Concentrations on Neuro- and Ototoxicity in Cisplatin-Treated Survivors of Testicular Cancer

Abstract: A B S T R A C T PurposeCisplatin-induced neurotoxicity and ototoxicity (NTX) are important adverse effects after chemotherapy for testicular cancer (TC). Although serum platinum is measurable years after therapy, its impact on NTX has not been evaluated. Patients and MethodsIn all, 169 cisplatin-treated survivors of TC provided blood samples at Survey I and reported NTX during Survey I (1998Survey I ( -2002 and Survey II (2007. Serum platinum was quantified by inductively coupled plasma mass spectrometry. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 58 publications
3
96
1
Order By: Relevance
“…61 Nevertheless, 20% of patients with metastatic disease cannot be cured, 62 and cDDP displays severe toxicities, for example, neurotoxicity. [37][38][39] This work indicates that HDACi and cDDP synergistically induce cell death in several testicular cancer-derived cell lines (GH, Susa, 1618-K). This raises the perspective of clinically using HDACis on testicular cancers that do not respond sufficiently to current standard therapeutic regimens.…”
Section: Catarrhinimentioning
confidence: 99%
“…61 Nevertheless, 20% of patients with metastatic disease cannot be cured, 62 and cDDP displays severe toxicities, for example, neurotoxicity. [37][38][39] This work indicates that HDACi and cDDP synergistically induce cell death in several testicular cancer-derived cell lines (GH, Susa, 1618-K). This raises the perspective of clinically using HDACis on testicular cancers that do not respond sufficiently to current standard therapeutic regimens.…”
Section: Catarrhinimentioning
confidence: 99%
“…Both studies documented a significant relationship between increasing concentrations of residual serum Pt and the severity of neurotoxicity in testicular cancer survivors treated with cisplatin-based chemotherapy, even when analyses were adjusted for initial cumulative cisplatin dose (3,4). The long-term persistence of increased serum Pt concentrations has been known for several decades, with investigations documenting amounts up to 1000-fold greater than in unexposed controls (2,5,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that a cumulative dose of platinum administered intravenously is associated with a number of these adverse effects, it is also recognized that in European populations, platinum concentrations remain significantly increased in serum years after chemotherapy completion (2)(3)(4). Moreover, Brouwers et al (5) showed that these circulating platinating agents remain partly reactive.…”
Section: Impact Statementmentioning
confidence: 99%
“…It has educational, vocational, and social consequences that may vary by age of onset (Bertolini et al, 2004;Brock et al, 2012;Langer, am Zehnhoff-Dinnesen, Radtke, Meitert, & Zolk, 2013;Travis et al, 2014). Tinnitus, which may interfere with sleep, daily function, and quality of life (Sprauten et al, 2012), is another important hearing outcome that is common following platinum chemotherapy.…”
Section: Discussionmentioning
confidence: 99%